2021
DOI: 10.22543/7674.82.p245251
|View full text |Cite
|
Sign up to set email alerts
|

Role of emotional intelligence in job performance of healthcare providers working in public sector hospitals of Pakistan

Abstract: Objective. To determine the association between emotional intelligence (EI) and job performance (JP) of health care providers (HCPs). Methods. Healthcare professionals from various hospitals were chosen for a crosssectional study. The survey was conducted using a three-part questionnaire including the demographic profile, Wong and Law Emotional Intelligence (EI) Scale, and an individual work performance (JP) questionnaire. The relationship of predictor variables on JP was sought by applying Chi-square test and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In addition, teachers with high empathy will also be easy to work together and collaborate according to school rules and procedures to help achieve contextual performance quickly. These findings were consistent and confirmed several previous studies that emotional intelligence influences contextual performance (e.g., Li & Lin, 2021;Rajapakshe & Jayaratne, 2021;Zaman et al, 2021;Schlaegel et al, 2022).…”
Section:  Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, teachers with high empathy will also be easy to work together and collaborate according to school rules and procedures to help achieve contextual performance quickly. These findings were consistent and confirmed several previous studies that emotional intelligence influences contextual performance (e.g., Li & Lin, 2021;Rajapakshe & Jayaratne, 2021;Zaman et al, 2021;Schlaegel et al, 2022).…”
Section:  Results and Discussionsupporting
confidence: 92%
“…Teachers' contextual performance, among others, can be affected by emotional intelligence. Previous studies indicated that emotional intelligence affects contextual performance (Sendaro & Baharun, 2020;Bilal et al, 2021;Grobelny et al, 2021;Li & Lin, 2021;Rajapakshe & Jayaratne, 2021;Zaman et al, 2021;Schlaegel et al, 2022). Moreover, in the educational context, emotional intelligence is also related to teaching effectiveness (Shahid, 2015) and academic performance (Sanchez-Alvarez, 2020).…”
Section: Emotional Intelligence and Contextual Performancementioning
confidence: 97%
“…Suleman (2020) investigated the relationship of EI with job satisfaction among school teachers. Zaman(2021) has done study on the role of EI with job performance among healthcare workers (doctors and nurses). Therefore, it is evident that there is paucity of scientific literature in the local population in particular the banking sectors in our Pakistani population.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare providers' ability to build EI is just as important as their medical training and experience (Eriguc & Kose, 2013). Consequently, EI has recently engendered great interest in the medical community and is now considered a non-cognitive function (Zaman et al, 2021). Healthcare employees must have a wide range of abilities, including empathising with others, communicating effectively, making intelligent decisions, and maintaining positive working relationships with co-workers and patients.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare employees must have a wide range of abilities, including empathising with others, communicating effectively, making intelligent decisions, and maintaining positive working relationships with co-workers and patients. Many people are curious about the connection between EI and work success, but little research has been undertaken (Zaman et al, 2021). Karimi et al (2021) suggested that employees with higher levels of EI can provide a high quality of care to patients in the aged care industry and that EI improves the psychological empowerment and wellbeing of aged care employees.…”
Section: Introductionmentioning
confidence: 99%